NPT and the developing countries - Mishra, Jita (New Delhi, 2008)
Addressing the security concerns of developing countries like India, Pakistan, North Korea, and Iraq, this book examines the key factors instrumental in the proliferation of nuclear weapons. It studies the conceptual dimensions of non-proliferation and highlights the discriminatory nature of the Non-Proliferation Treaty (NPT). It attempts to probe new areas concerning national priorities, specific assessments and geo-strategic compulsions of these four developing nations in their approach towards the NPT The book will be of great use for policy makers and students of international relations.
Keywords: Treaty on the Non-Proliferation of Nuclear weapons